CO-OPERATIVES, THEIR POLITICAL ECONOMY, AND THE PROPOSED HARMONIZATION OF LAWS: A CASE FOR AFRICA - Akanji , Ajibola Anthony (International Journal of Cooperative Law, 2023)
The materialists conceptualize history within the context ofconflict relating to classes and socio-economic forces. Within history, co-operatives as socio-economic forces have played significant roles in the stages of developmentand have gained relevance in the class struggles that have ensued. Hence, co-operatives qualify as products and players in the dynamic and evolving Marxism versus capitalism struggles. As a result, co-operative laws are a reflection of the climax and anti-climax of class struggles, but in African’s case a body of defective legal framework is presented. These deficiencies currently constitute hindrances to the optimal utilization of some projected benefits from the harmonization of co-operative laws. With Nigeria as the primary case study,this work critically reviews extantliterature that problemitises the study, adoptingthe descriptive research methodology. The political economy of African co-operatives is appraised, with the following preliminary findings: African co-operatives have been impacted with variants of Marxism and capitalism through military and civil rules in the postcolonial era, both ideologies have influences on African co-operative laws, with capitalism having the better share, African co-operatives possess symptoms of peasant Marxism, but are regulated by laws highly influenced by imperial-capitalism, this ideological deficitis at the foundation of co-operative law in Africa. Although reviews and advancements are currently being attempted through the harmonization of co-operative legislations within the regions of Africa, regional frameworks have not been particularly successful on the continent. Therefore, an appraisal of the political economy of African co-operatives and its influences on co-operative laws is recommended as a primary remedial. Further, an apex international legal framework which addresses local peculiarities that influences such political economy, and by consequence sub-national and national co-operative legislations is recommended. A Universal Charter for Co-operative Societies fashioned after the Universal Charter on Human Rights 1948 is then proposed for further development.